2018
DOI: 10.1002/chem.201703533
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Properties of Tin‐Containing Conjugated Heterocycles

Abstract: Heterocycles that contain tin atoms can be aromatic in a similar sense to well-known aromatic compounds such as benzene or thiophene, but such examples are rare. However, due to the low-lying σ*-orbitals of the tin-substituent bond in stannoles, they are capable of σ*-π* conjugation in a way that is exclusive to heavier element containing heterocycles. This makes stannoles very interesting alternatives for purely organic heterocycles in material applications, in which optoelectronic properties are of interest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 112 publications
(208 reference statements)
0
12
0
Order By: Relevance
“…In addition to being highly selective, Cp 2 Zr(py)(η 2 ‐btmsa) tolerates functional groups. This was shown by Staubitz and co‐workers for the case of tin containing conjugated hetrocycles for the synthesis of a polymer containing stannole units in the main chain . The bis(thienyl) substituted octadiyne was converted in an intermolecular coupling reaction to the zirconacyclopentadiene with the iodide substituents remaining intact.…”
Section: New Reactions Of Formed Coupling Productsmentioning
confidence: 99%
“…In addition to being highly selective, Cp 2 Zr(py)(η 2 ‐btmsa) tolerates functional groups. This was shown by Staubitz and co‐workers for the case of tin containing conjugated hetrocycles for the synthesis of a polymer containing stannole units in the main chain . The bis(thienyl) substituted octadiyne was converted in an intermolecular coupling reaction to the zirconacyclopentadiene with the iodide substituents remaining intact.…”
Section: New Reactions Of Formed Coupling Productsmentioning
confidence: 99%
“…However, size is not the only change; optophysical properties can also be influenced substantially. For example, it has been shown that for cyclopentadiene analogs, in which the sp 3 substituted C atom is replaced by a heavier group 14 element, the HOMO-LUMO gap (HOMO = highest occupied molecular orbital; LUMO = lowest unoccupied molecular orbital) is reduced due to σ*-π* conjugation [2,3,4,5,6]. Due to our interest in both main group chemistry and photoswitchable molecules, we systematically investigated the influence that could be exerted by tetrels in the ortho -position of azobenzenes, as well as the structural influences this substitution might trigger: Azobenzenes are thermally and photochemically stable molecular switches that can undergo a reversible trans – cis isomerization under illumination.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, π‐conjugated polymers containing silole units are reported to exhibit remarkably low LUMO energy levels which enable their potential application to the electron‐transporting layers in the electroluminescence (EL) devices . Heteroles containing heavier group 14 elements such as germole and stannole are also expected to serve as electron‐accepting building blocks through the analogous σ*‐π* orbital interactions . Nevertheless, within the knowledge of the authors, only one preceding work on the synthesis of a stannole‐containing π‐conjugated polymer has been described by Staubitz and coworkers, in which a 1,1‐diphenylstannole‐containing polymer was obtained by the Stille coupling reaction of a relatively stable 1,1‐diphenylstannole‐containing aryl diiodide with a distannylthiophene and the resulting polymer exhibits a relatively narrow band gap (1.7 eV) in film .…”
Section: Methodsmentioning
confidence: 99%